Chemical probes targeting the kinase CK2: a journey outside the catalytic box. Issue 20 (7th April 2021) - Iegre, Jessica; Atkinson, Eleanor L.; Brear, Paul D.; Cooper, Bethany M.; Hyvönen, Marko; Spring, David R.
Abstract : An up-to-date and comprehensive review on chemical probes targeting the important kinase CK2. Abstract : CK2 is a protein kinase that plays important roles in many physio-pathological cellular processes. As such, the development of chemical probes for CK2 has received increasing attention in the past decade with more than 40 lead compounds developed. In this review, we aim to provide the reader with a comprehensive overview of the chemical probes acting outside the highly-conserved ATP-site developed to date. Such probes belong to different classes of molecules spanning from small molecules to peptides, act with a range of mechanisms of action and some of them present themselves as promising tools to investigate the biology of CK2 and therefore develop therapeutics for many disease areas including cancer and COVID-19.